The effect of students' exam anxiety on high school entrance exam success: The moderator role of parental exam anxiety - Ahmet Genç; Esat Şanlı (Journal of Pedagogical Research, 2023)
This research is a causal study that examines the moderator role of parental exam anxiety in the relationship between eighth-grade students' exam anxiety and high school entrance exam success. Participants of the study consisted of a total of 353 eighth-grade students attending seven different middle schools in the North region of Türkiye. Personal Information Form, Test Anxiety Scale for Parents and Children were used as data collection tools. Pearson Product-Moment Correlation Coefficients were calculated for descriptive analysis of tha data. Bootstrap method was used to estimate sampling distributions. In the study, 5000 bootstrap were used and the confidence intervals were determined as %95. Analyses showed that parental exam anxiety played a moderator role in the relationship between children's exam anxiety and high school entrance exam scores.